Elevated plasma levels of factor VIII enhance arterial thrombus formation on erosive smooth muscle cell-rich neointima but not normal intima in rabbits - Sugita, Chihiro; Maekawa, Kazunari; Gi, Toshihiro; Oguri, Nobuyuki; Nakamura, Eriko; Furukoji, Eiji; Azuma, Minako; Asada, Yujiro; Yamashita, Atsushi (Thrombosis research, 2024)
Plaque erosion, a type of coronary atherothrombosis, involves superficial injury to smooth muscle cell (SMC)-rich plaques. Elevated levels of coagulation factor VIII (FVIII) correlate with an increased ischemic heart disease risk. FVIII may contribute to thrombus formation on eroded plaques. We aimed to elucidate the role of elevated FVIII in arterial thrombus formation within SMC-rich neointima in rabbits. We assessed the effect of recombinant human FVIII (rFVIII) on blood coagulation in vitro and platelet aggregation ex vivo. An SMC-rich neointima was induced through balloon injury to the unilateral femoral artery. Three weeks after the first balloon injury, superficial erosive injury and thrombus formation were initiated with a second balloon injury of the bilateral femoral arteries 45 min after the administration of rFVIII (100 IU/kg) or saline. The thrombus area and contents were histologically measured 15 min after the second balloon injury. rFVIII administration reduced the activated partial thromboplastin time and augmented botrocetin-induced, but not collagen- or adenosine 5′-diphosphate-induced, platelet aggregation. While rFVIII did not influence platelet-thrombus formation in normal intima, it increased thrombus formation on SMC-rich neointima post-superficial erosive injury. Enhanced immunopositivity for glycoprotein IIb/IIIa and fibrin was observed in rFVIII-administered SMC-rich neointima. Neutrophil count in the arterial thrombus on the SMC-rich neointima correlated positively with thrombus size in the control group, unlike the rFVIII group. Increased FVIII contributes to thrombus propagation within erosive SMC-rich neointima, highlighting FVIII's potential role in plaque erosion-related atherothrombosis. •Recombinant VIII (rFVIII) does not affect thrombus formation on normal intima.•rFVIII enhances platelet-fibrin thrombus on smooth muscle cell-rich neointima.•Enhanced thrombosis under elevated FVIII is neutrophil-independent.